2017
DOI: 10.1016/j.agee.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying land use contributions to suspended sediment in a large cultivated catchment of Southern Brazil (Guaporé River, Rio Grande do Sul)

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 39 publications
6
42
1
7
Order By: Relevance
“…In the grassland catchment, considering the approach with the best tracer combination (GSRV), the main sediment source was natural grassland (84%), followed by oats pasture fields (14%) and stream channel (2%). These results are in agreement with those obtained in other studies conducted in rural catchments of Rio Grande do Sul, Southern Brazil, which indicated that cropland (91 ± 15%) was the main source of sediment and low stream channel contributions (5 ± 2%) (Tiecher, Minella, et al, 2017). The dominance of natural grassland originating sediment is consistent with the large surface area occupied by this potential source in the catchment and with the high erosion rates observed in these areas compared to those found in the eucalyptus catchment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the grassland catchment, considering the approach with the best tracer combination (GSRV), the main sediment source was natural grassland (84%), followed by oats pasture fields (14%) and stream channel (2%). These results are in agreement with those obtained in other studies conducted in rural catchments of Rio Grande do Sul, Southern Brazil, which indicated that cropland (91 ± 15%) was the main source of sediment and low stream channel contributions (5 ± 2%) (Tiecher, Minella, et al, 2017). The dominance of natural grassland originating sediment is consistent with the large surface area occupied by this potential source in the catchment and with the high erosion rates observed in these areas compared to those found in the eucalyptus catchment.…”
Section: Discussionsupporting
confidence: 93%
“…Franz, Makeschin, Weib, & Lorz, 2014; Le Gall et al, 2016; Miguel, Dalmolin, Pedron, & Moura‐Bueno, 2014; Miguel, Dalmolin, Pedron, Moura‐Bueno, & Tiecher, 2014; Minella, Merten, & Clarke, 2009; Minella, Walling, & Merten, 2014; Tiecher, Caner, et al, 2017; Tiecher et al, 2014, 2015, 2018; Tiecher, Minella, et al, 2017). Tiecher, Minella, et al (2017) investigated the sediment source contributions in two paired agricultural catchments with different proportions of riparian vegetation and wetlands and similar proportions of crop fields. Stream channel were the main source of sediments (49 ± 26%) in the catchment with the lower proportion of riparian vegetation and wetlands, while in the other study site with a higher proportion of riparian vegetation, the stream channel contribution amounted to only 23 ± 14%.…”
Section: Introductionmentioning
confidence: 99%
“…The model used had only two boundary conditions, wherein (a) the sum of the sources contribution should be equal to 100% and (b) the contribution of each source may not be less than 0% and not higher than 100%. Further details on this procedure can be found in Tiecher, Minella, et al ().…”
Section: Methodsmentioning
confidence: 99%
“…In addition to modeling and monitoring studies, the sediment fingerprinting technique was shown to provide a powerful tool to identify sediment sources in Brazil (Miguel, Dalmolin, Pedron, Moura‐Bueno, & Tiecher, ; Minella, Merten, Reichert, & dos Santos, ; Minella, Merten, Walling, & Reichert, ; Minella, Walling, & Merten, , ; Tiecher et al, ; Tiecher, Caner, et al, ; Tiecher, Caner, Minella, & dos Santos, ; Tiecher, Caner, Minella, Bender, & dos Santos, ; Tiecher, Minella, et al, ) and elsewhere in the world, such as in France (Foucher et al, ; Legout et al, ; Navratil, Evrard, Esteves, Legout, et al, ; Poulenard et al, ), Mexico (Evrard et al, ), South Africa (Foster, Boardman, & Keay‐Bright, ), Zambia (Walling, Collins, Sichingabula, & GJL, ), Canada (Barthod et al, ; Koiter et al, ; Stone, Collins, Silins, Emelko, & Zhang, ), United States (Devereux, Prestegaard, Needelman, & Gellis, ), United Kingdom (Collins, Walling, Webb, & King, ; Pulley, Foster, & Antunes, ; Smith & Blake, ), Spain (Brosinsky, Foerster, Segl, & Kaufmann, ), Luxemburg (Martínez‐Carreras et al, ), Turkey (D'Haen et al, ), Tunisia (Ben Slimane et al, ), Iran (Haddadchi, Nosrati, & Ahmadi, ), and Australia (Laceby, McMahon, Evrard, & Olley, ; Olley, Burton, Smolders, Pantus, & Pietsch, ; Wilkinson, Hancock, Bartley, Hawdon, & Keen, ). Therefore, the objective of the current study is to quantify the contribution of sources supplying sediment to the river in a catchment characterized by the widespread implementation of NT since the 1990s in Southern Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Ceretta et al (2010b) and Lourenzi et al (2014a), if well managed, the runoff water from the soil surface under NT does not result in large soil losses by erosion, which would remove P as particulate P. Unfortunately, this is not the case of most fields in the state of Rio Grande do Sul, Southern Brazil, where cropland is unambiguously the main source delivering sediments into the rivers (Tiecher et al, 2015(Tiecher et al, , 2017 The increase in SMB-P observed with the increase in PS rates (Table 4) is a beneficial effect, for delaying phosphate adsorption by the soil, and after cell death and lysis, it releases P to the soil solution for plant uptake (Martinazzo et al, 2007;Gatiboni et al, 2008a). The results indicated a high linear correlation coefficient between SMB-P × Av-P and SMB-P × Total-P, because the soil microbial biomass is a dynamic compartment that immobilizes P when P availability increases in the soil solution .…”
mentioning
confidence: 90%